User Interface Evaluation of the Business Development Center Website at UIN Syarif Hidayatullah Jakarta: A Content, Visual, and Navigation Perspective - Sobri, Muhammad; Subchi, Imam (Jurnal Teknik Informatika (Jutif), 2025)
The business development center State Islamic University Syarif Hidayatullah Jakarta (UIN Jakarta) as the main manager of the campus's business lines that functions to manage, develop, generate funding sources, underpin the development of business ideas and implement business ideas that have been designed and agreed upon by the UIN Jakarta Leadership and other stakeholders. This study aims to evaluate the business development center website UIN Jakarta from a user interface perspective. This study uses a questionnaire containing to evaluate the user interface in terms of content, visuals and navigation. Based on the questionnaire data that has been filled out by respondents, the most significant findings from each aspect. The content aspect, valued at 76.3% for information regarding the vision, mission, work programs, and the foreword of the head of the center are presented completely and easily accessible, but 63.2% complained that some parts of the service are not detailed enough. The visual aspect, valued at 63.2% for the consistent campus color identity on the background and title, but 60.5% complained that the contrast of white text on the dark gray background area is less user-friendly. While the navigation aspect, valued at 71.1% for the about, services, and gallery features are clearly visible, but 63.2% complained that there is no visual highlight for the menu being accessed. This study contributes to the development of the business development center website UIN Jakarta based on responses from participants completed the questionnaire to be more optimal and provide all information regarding the business units at UIN Jakarta as a form of promotion to be known and serve the wider community. In addition, this study presents innovations for developing a user interface evaluation framework for institution websites, particularly those related to business development center in state islamic universities.